Sodelovanje staršev z vrtcem kot dejavnik kakovosti vrtca - Lepičnik Vodopivec, Jurka (Revija za elementarno izobraževanje, 2010)
Quality in kindergartens from the perspective of parents - a case study. The article elaborates on the aspect of quality in kindergartens from the perspective of parents, who are important co-creators of quality. Recent research findings emphasize the role of parents in this process: that parents should be involved both in the process of quality control as well as in the process of quality creativity in kindergartens. Our empirical research done on the aspects of quality in kindergartens was conducted by means of a questionnaire using a sample of parents. We established that parent-teacher meetings are relatively frequent in kindergarten (2,3,4 - times annually or even more frequently), which means that the possibilities for cooperation between parents and educators can be realized more easily. The educators also use the billboards relatively frequently in order to give information to the parents. Day to day communication between parents and educators, as an important factor of quality in kindergarten, is a common practice. The educators also enable the parents to participate in interesting activities (shows, trips, picnics and workshops), which we believe are important activities for parents, as they able them to see their children in various situations that are present in kindergarten.